Analisis dan Perancangan Aplikasi Administrasi User Pada Server Radius Berbasis Web (Studi Kasus Binus@Ccess) - Lukito, Rony Baskoro; Feriaty, Elly; Salim, Suyatno; Kurniali, Sartika (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Bina Nusantara University as one of the information technology-based educational institutions in Indonesia have used the Internet in learning activities. To meet the needs of Internet access, Binus provides students with BiNus@ccess Premium service. BiNus@ccess Premium already have an application to help admin to user management with the help of a centralized accounting system (which is provided by the RADIUS server). However, applications that use is still limited in some ways so that there are still many manual processes. Therefore we need an application that serves to replace the existing application but still supports the existing system. The methodology used to admin consists of interviews, questionnaires to users, observation to analyze the problem, designing application solutions, and evaluation by distributing questionnaires to the admin. With the RSIM applications, manual administrative processes can be eliminated because the user can perform the registration process and the addition of its own loans through the application by themselves. RSIM Applications can also provide solutions for prepaid voucher sales system because it provides the ability to generate a voucher, print vouchers, and see the voucher reports, list payment, and the sale report. Suggestions for further development is to create applications for the sale of voucher system with e-commerce or SMSgateway..